Cobertura vegetal e qualidade ambiental na área urbana de Santa Maria (RS) - Alves, Daniel Borini (2012)
The disregard of the natural attributes in the process of urbanization reflects in many cities undergoing a profound process of loss of environmental quality, challenging the most different researchers and professionals discussing the urban and environmental planning to seek alternatives to assist in the management of conflicts in relationship between society and nature in urban areas. Related to a number of environmental features, the presence of vegetation appears to be essential in the composition of the urban landscape, and from it is possible that many environmental problems can be mitigated or resolved. In this context, this research sought to investigate the variation of the distribution of trees in the urban area of Santa Maria in the last forty-five years, highlighting its potential for ensuring the thermal and hydrological feature of the city. Sought in the interpretation of the urban landscape from the geossistemic perspective methodological support to achieve the proposed objectives, dialoguing with the knowledge transmitted in discussions involving the urban ecology and nature conservation in cities. Therefore, we decided a review of theoretical and methodological concepts and processes involved in the investigation, following a characterization with natural and historical-territorial urban landscape of Santa Maria. Continued with the temporal and spatial analysis of local urban landscape, observing the variation of the horizontal structure of vegetation in recent decades (1966-2011), and defining the landscape units in the urban area of Santa Maria (Geofacies within Geosystem). After that, we selected four pilot areas in which we analyzed the contribution of vegetation cover in the performance of thermal and hydrological features, contextualized with results of previous studies in Santa Maria on the thermal field on the characteristics and local runoff in the city. The results show that the canopy had a significant decrease in recent decades, reaching a record loss of 12.38% of total vegetation cover between 1980 and 2011, resulting in a configuration of small fragments and isolated trees in areas called Geofácie densely built. It is observed that the percentage of woody vegetation found for 2011 of 32.90% for the entire urban area, due to very high levels of afforestation of Geofacies situated in the rim of hills and mountains of evidence, that allow to hide the high degree fragmentation observed in built up areas. As for the thermal analysis of the variability and the discharge control in the pilot areas, we can see clearly the contribution of vegetation cover in temperatures of softening in hot weather and its potential for decreasing the rate of runoff in episodes of precipitation. Discussed the benefits observed, measured and proven plant cover in urban areas, it is essential to improving the environmental quality of Santa Maria, which are deployed new green areas, establishing criteria for the proper disposal of trees to maximize their effects positive.